The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/jf405573e
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Lung Cancer Cell Apoptosis through a p53 Pathway by [6]-Shogaol and Its Cysteine-Conjugated Metabolite M2

Abstract: Dietary chemoprevention of cancer offers the possibility to suppress or inhibit cancer growth before it develops into more advanced and lethal stages. To this end, identification of novel compounds and their mechanisms of action is constantly needed. In this study, we describe that a major component of dry ginger (Zingiber officinalis), [6]-shogaol (6S), can be quickly metabolized in A549 human lung cancer cell line. One of the resulting metabolites, the cysteine-conjugated 6S (M2), exhibits toxicity to cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…It was reported that 6‐gingerol attenuated oxidative damage on cell death of neurons (Lee, Park, Kim, & Jang, ), while it damaged the mitochondrial function resulting in cellular apoptosis in several other cell types (Mansingh, O J, Sali, & Vasanthi, ; Nigam, Bhui, Prasad, George, & Shukla, ; Yang et al., ). 6‐Shogaol was consistently reported to damage mitochondrial function of cells (Annamalai, Kathiresan, & Kannappan, ; Chen et al., ; Warin, Chen, Soroka, Zhu, & Sang, ). We hypothesized that the concentration of 6‐gingerol and 6‐shogaol used in various experimental settings may cause the above inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 6‐gingerol attenuated oxidative damage on cell death of neurons (Lee, Park, Kim, & Jang, ), while it damaged the mitochondrial function resulting in cellular apoptosis in several other cell types (Mansingh, O J, Sali, & Vasanthi, ; Nigam, Bhui, Prasad, George, & Shukla, ; Yang et al., ). 6‐Shogaol was consistently reported to damage mitochondrial function of cells (Annamalai, Kathiresan, & Kannappan, ; Chen et al., ; Warin, Chen, Soroka, Zhu, & Sang, ). We hypothesized that the concentration of 6‐gingerol and 6‐shogaol used in various experimental settings may cause the above inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the functional binding sites existing in the promoter region, the expression of caspase-1 gene is demonstrated to be activated by several transcriptional factors, such as IRF-1, signal transducer and activator of transcription (STAT) 1, p53, and p73 and E26 transformation-specific sequence 1 (Ets-1) [ 27 ]. On the other hand, 6-shogaol was demonstrated to induce lung cancer cell apoptosis through activating p53 pathway and to increase the expression of p21, p27, SOCS1, and IRF1 in prostate cancer cells [ 28 , 29 ]. The inducing effect of these effective ginger phytochemicals, especially 6-shogaol, on caspase-1 gene expression might be partially attributed to their activating effect on p53 and IRF1.…”
Section: Discussionmentioning
confidence: 99%
“…6-shogaol [1-(4-hydroxy-3-methoxyphenyl)-4-decen-3-one] found in small quantities in fresh ginger is even more abundant in processed ginger. Accumulating in vitro evidence suggests the involvement of multiple signaling pathways by which 6-shogaol suppresses growth of human cancer cells (Weng et al, 2010;Saha et al, 2014;Warin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%